AVIATION ENTERPRISES RESTRUCTURING AS A WAY TO AVOID BANKRUPTCY - Kozyreva, Valentyna P.; Armash, Nadiya O. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Purpose: the task of scientific research is to determine legal methods to avoid the bankruptcy of aviation enterprises. Particularly, the article deals with the process of bail-out before the initiation of a bankruptcy case as one of the effective measures to avoid insolvent debtor of the aviation enterprises. Methods: comparative and systemic methods for disclosing the restructuring of aviation enterprises. Discussion: it was estimated that the most effective ways to avoid bankruptcy of the aviation enterprise are the bail-out of the debtor before the initiation of a bankruptcy case. The bail-out procedure is a system of measures to restore the debtor’s solvency, which can be carried out by the founders of the debtor’s company (participating partners and shareholders), owner of debtor’s property (the body authorized to manage the property), the debtor’s lender, other persons for the purpose to avoid bankruptcy of the debtor by taking organizational, economic, managerial, investment, technical, financial, economic, legal measures in accordance with the law until the violation of the laws in the case of bankruptcy.